Pakistan : Contingent Liabilities from Public Private Partnerships - World Bank (Washington, DC, 2013)
This final report is the fourth and final deliverable in Castalia's assignment, funded by the World Bank, to improve how contingent liabilities are managed in Pakistan. The report presents recommendations on how Pakistan should improve its policies and processes for issuing and managing contingent liabilities associated with public private partnerships (PPPs) in infrastructure. The contents of this report are organized as follows: section two explains why it is important for Pakistan to establish sound policies for managing contingent liabilities, based on the Government's existing exposure and gaps in the policies and processes that are currently in place. The Status Quo Report presented in appendix A provides an assessment of the Government's exposure to contingent liabilities and the existing policies and processes that are in place. Section three explains how Pakistan can better manage contingent liabilities by presenting recommendations to eight specific functions that will strengthen existing PPP policies. Section four analyzes options for who should perform the functions for managing contingent liabilities, and explains why we recommend empowering existing institutions in the preferred institutional framework. Section five presents the steps we suggest that the Government follows to implement these recommendations and operationalize an effective contingent liabilities management framework. Finally, section six presents assessment of international experience and good practice in managing contingent liabilities to provide additional context for recommendations in Pakistan. Appendix A includes the Status Quo Report from the first stage of this assignment. Appendix B includes a summary of the stakeholder consultation workshop conducted in Islamabad on July 21 to receive feedback on the draft recommendations for this assignment.